The Predictive Role of Psychological Status and Disease Severity Indexes on Quality of Life Among Patients with Non-CF Bronchiectasis - (:unkn) unknown (AVES, 2022)
OBJECTIVE: Bronchiectasis is a chronic suppurative lung disease that significantly impacts the patients’ quality of life. The aim of this study is to evaluate the relationship between quality of life and patient’s psychological status and bronchiectasis disease severity indexes in patients with non-cystic fibrosis bronchiectasis. We also aimed to investigate the validity and reliability of Turkish version of Quality of Life Questionnaire-Bronchiectasis (V3.1) in Turkish adult bronchiectatic patients. MATERIAL AND METHODS: In total, 90 stable non-cystic fibrosis bronchiectatic adult patients were enrolled in this study. At baseline, dyspnea score, body mass index, lung function tests, sputum cultures, number of exacerbations and hospital admissions, and disease severity indexes were recorded. All of the participants underwent quality of life assessment using both Quality of Life Questionnaire-Bronchiectasis V3.1 and Short Form-36 questionnaires, and psychological status was evaluated by using Hospital Anxiety and Depression Scale. RESULTS: In all study participants, anxiety was diagnosed in 27/90 (30%) of patients, and depression was diagnosed in 37/90 (41%) of patients. Patients with anxiety and depression had lower quality of life scores in various domains (P = .026-.001), and Hospital Anxiety and Depression Scale scores negatively correlated with several quality of life domains (r = −0.216 to 0.343). Female patients had higher risk for depression (55% vs 22%, P = .002) and worse quality of life than males (P = .016-.038). Several life quality scores of both instru-ments were worse in patients with moderate–severe disease severity indexes when compared with those of mild groups. Moreover, Turkish version of newly described Quality of Life Questionnaire-Bronchiectasis V3.1 questionnaire was found to be a reliable and valid instrument to evaluate the quality of life. CONCLUSION: These results emphasize the importance of mental health and disease severity as significant determinants of the life quality in patients, particularly female patients with non-cystic fibrosis bronchiectasis. © 2022 by Turkish Thoracic Society.
Keywords: Anxiety; Depression; Non-CF bronchiectasis; Quality of life